The Pandemy and the precarization of working conditions of higher education teachers (Research, Society and Development, 2021)
This text seeks to point out and reflect on some of the impacts of the COVID-19 Pandemic on the working conditions of higher education teachers in Brazil. With the need for social isolation and the impossibility of maintaining classroom classes, the teaching-learning environment was migrated to the online format, which has been implying (and evidencing) a precariousness not only of teaching, but also of conditions teachers' workload, increasingly overloaded. This research was developed through qualitative research, with analysis of official documents and literature review. This study is justified by the need to reflect on the profound changes imposed by the pandemic and its effects on the quality of teaching-learning and teaching work conditions.